A STUDY ON THE FACTORS INFLUENCING INVESTORS DECISIONS IN INVESTING IN SHARES WITH SPECIAL REFERENCE TO GENDER IN BIKANER - Rani, Jyoti; Saxena, Pankhuri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With a sample of one hundred investors in Bikaner, Rajasthan, the current study aims to identify the key determinants of their share investment decisions. Behavior finance is a revolution in the finance business that has emerged and developed. When making decisions about their investments, investors hardly ever act rationally. Essentially, investors take action based only on the facts at their disposal. Prior to making an investment in the equities market, a great deal of thought must be given. One must take ratio analysis into account. When making an investment in the capital market, one must consider a comprehensive economic study as well as the technical and financial evaluation of the company. The objective of research project is to ascertain how male and female investors perceive different factors that should be taken into account when making equity market investments. The aim of this research is to summarize how different types of investors—male and female—feel about different investing options. From the cities of Bikaner, the researchers have collected 52 female and 47 male contributors. To verify the hypothesis, the study employs mean scores and an independent t-test. The article ends by recommending that, before purchasing shares, investors attempt to conduct fundamental, technical, and financial research. Investing in various assets requires investors, regardless of gender, to consider all available options. While allocating their money, investors ought to consider all options. Investors should select riskier or less risky assets based on their age, as certain investments carry a higher risk than others.